2014
DOI: 10.1134/s002626171406023x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and functions of the extracellular polymer matrix of bacterial biofilms

Abstract: The data on the composition and structure of the components comprising the extracellular poly mer matrix of bacterial biofilms, the role of these components, and their functions in the biofilm are reviewed. The main biochemical mechanisms regulating the biosynthesis of biofilm matrix are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Indeed, when the RT4 strain was grown in the more polar medium (BHI) it was forming biofilm in abundance whereas this activity was reduced in RCM and even more in SLM. Biofilm is a defence mechanism for bacteria and a strategy to resist in unfavorable environments (Zhurina, Gannesen, Zdorovenko, & Plakunov, ), as for the RT4 in BHI. The same was observed, but at the opposite, with the RT6 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when the RT4 strain was grown in the more polar medium (BHI) it was forming biofilm in abundance whereas this activity was reduced in RCM and even more in SLM. Biofilm is a defence mechanism for bacteria and a strategy to resist in unfavorable environments (Zhurina, Gannesen, Zdorovenko, & Plakunov, ), as for the RT4 in BHI. The same was observed, but at the opposite, with the RT6 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work revealed that the EPS produced by B . licheniformis CGMCC2876 contains an abundant amount of amino sugars (Xiong et al, ), and polysaccharides can also be used as carbon or nitrogen sources(Ferreira et al, ; Zhurina et al, ). Similarly, there are studies reporting that microorganisms secrete γ‐PGA depolymerase to degrade γ‐PGA as a nutrient source when the medium only contains γ ‐PGA (Jeong et al, ; Kunioka and Goto, ).…”
Section: Discussionmentioning
confidence: 99%
“…Like arthropods, bacteria use amyloids as a structural scaffold for biofilm formation. Biofilms are dense communities of bacteria in which cells associate with surfaces and each other using a self‐produced extracellular matrix (EM) composed of proteins, polysaccharides, and genetic material (Zhurina et al, ). Proteins in the biofilm EM may take on a variety of forms, but amyloid structures are common, and recent research suggests that many multi‐drug resistant (MDR) bacterial strains utilize amyloid fibrils to facilitate bacterial aggregation and biofilm formation as an underlying mechanism of virulence (DePas and Chapman, ; Romero and Kolter, ; Syed and Boles, ; Zhou et al, ).…”
Section: Functional Amyloidsmentioning
confidence: 99%